Respostas
respondido por:
4
4^x - 2 . 2^x - 8 = 0.
(2²)^x - 2.2^x - 8 = 0.
(2^x)² - 2.2^x - 8 = 0. Fazendo 2^x = y, temos
y² - 2y - 8 = 0
Δ = (-2)² - 4 . 1 . (-8) = 4 + 32 = 36
y= [-(- 2) +/- √36] /2 = [ 2 +/- 6]/2
y1 = (2 + 6)/2 = 4
y2 = (2 - 6)/2 = - 2
Substituindo em 2^x = y, temos:
2^x = 4
2^x = 2²
x = 2
f(x) = 2^(3x -2)
f(2) = 2^(3.2 -2) = 2^(4) = 16
(2²)^x - 2.2^x - 8 = 0.
(2^x)² - 2.2^x - 8 = 0. Fazendo 2^x = y, temos
y² - 2y - 8 = 0
Δ = (-2)² - 4 . 1 . (-8) = 4 + 32 = 36
y= [-(- 2) +/- √36] /2 = [ 2 +/- 6]/2
y1 = (2 + 6)/2 = 4
y2 = (2 - 6)/2 = - 2
Substituindo em 2^x = y, temos:
2^x = 4
2^x = 2²
x = 2
f(x) = 2^(3x -2)
f(2) = 2^(3.2 -2) = 2^(4) = 16
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás